Virgil's Map : Geography, Empire, and the Georgics - Kerrigan, Charlie (Bloomsbury Studies in Classical Reception Ser, 2020)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Contents -- Acknowledgements -- Abbreviations -- Introduction -- Part One Rome and the Roman Empire, 29 bce -- 1 The World and Its Peoples -- Cultural appropriation -- Peoples and places -- Thrace -- North Africa -- Iberia -- Illyria -- 2 Provincializing Rome -- Products and produce -- Arabian frankincense -- The Levant: balsam, bows, palms -- Ethiopian wool, Chinese silk -- Triumphal geography -- Provincializing Rome -- 3 Civil War -- The geography of civil war -- India -- Egypt -- 4 'All Italy' -- Italian landscapes: the ager Bruttius, Lucania, Campania -- The peoples of Italy: Volscians and Ligurians -- The peoples of Italy: Marsi, Samnites and the Social War -- Part Two Britain and the British Empire, c. 1840-1930 -- 5 An Aesthetic Trend -- The 'artistic perfection of the Georgics' -- Defending Virgil -- The 'poet of rural life' -- Scholarship and the First World War (1914-18) -- Modern scholarship -- 6 The Georgics Abroad -- Italy -- A Peloponnesian tour -- Ethiopia -- 'The Georgics of Algeria' -- 7 'Happy Farmers' -- J. A. Froude's Oceana -- The Irish People and the Irish Land -- India -- The Second South African War (1899-1902) -- 8 The Georgics at Home -- Land reform -- DORA -- The Georgics in wartime -- 'The Empire and the Land' -- Conclusion: Towards a Decolonizing Pedagogy of Latin Literature -- Appendix: The Geography of the Georgics -- Notes -- References -- Index of Passages from the Georgics -- Index.